The Adoption of Crowdfunding by Indonesia's Political Party: A Case Study on Partai Solidaritas Indonesia - Vatanasakdakul, Savanid; Azka, Muhamad Fatih (Jurnal Studi Pemerintahan, 2021)
This paper offers an analysis of crowdfunding adoption by political party in Indonesia to achieve its funding targets. This study's significance is that it will explore the phenomenon of the use of crowdfunding for political causes, which is an under-researched topic and provide a new contribution to knowledge that raises awareness of the potential and challenges of the use of crowdfunding by a political entity. By having a case study on Partai Solidaritas Indonesia (PSI), which is one of the political parties in Indonesia, this paper presents questions on the strength and weaknesses of PSI crowdfunding campaigns. It then draws analysis on the implications of this funding model beyond political votes. The findings suggest that PSI is not successful in managing its crowdfunding campaigns, and despite a high level of social media engagement, its campaign lacks coordination.